Hysteroscopic findings after laparoscopic and open myomectomy with or without uterine cavity breach: historical cohort study - Boudova, Barbora; Hlinecka, Kristyna; Lisa, Zdenka; Richtarova, Adela; Zizka, Zdenek; Mara, Michal (Minimally invasive therapy & allied technologies, 2022)
INTRODUCTION: The aim of this study was to evaluate hysteroscopic findings after laparoscopic and laparotomic myomectomy with a focus on the presence of postoperative intrauterine adhesions in groups of patients with and without perioperative uterine cavity breach (UCB). MATERIAL AND METHODS: This is a historical cohort study. Our database was searched to identify patients with UCB during myomectomy and matched the same number of patients after myomectomy without UCB to create a control group. All relevant data were retrieved from our medical records. In both groups, the results of follow-up hysteroscopy were analyzed. RESULTS: Low prevalence of intrauterine adhesions after myomectomy was observed in only 3.5% of the 170 patients in our samples. No significant difference in the occurrence of synechiae between the patients with and without UCB was found (2 vs. 4, RR 0.5, 95% CI 0.1-2.7, p = .341), nor was the difference in other hysteroscopic findings. Follow-up hysteroscopy was performed with slender optics and expandable casing system without need of any anesthesia in 87.1% of cases. CONCLUSIONS: According to our findings, the prevalence of post-myomectomy intrauterine adhesions after myomectomy is low. Our study did not demonstrate that UCB during myomectomy is a risk factor for the formation of intrauterine synechiae.
Keywords: leiomyom; leiomyoma; hysteroscopy; Uterine Myomectomy; těhotenství; Uterine Neoplasms; Cohort Studies; Leiomyoma; adheze tkání; Uterine Diseases; Laparoscopy; kohortové studie; ženské pohlaví; nádory dělohy; myomectomy; Humans; Tissue Adhesions; Pregnancy; hysteroskopie; nemoci dělohy; myomektomie; Fertility; intrauterine adhesions; Hysteroscopy; Female; laparoskopie; lidé